PENGARUH PENDEKATAN DISTRIBUTED PRACTICE DAN MASSED PRACTICE TERHADAP TEKNIK DASAR BERMAIN SEPAK BOLA (Studi Experimen pada Siswa SSB Yapora Pratama Pekanbaru) - Prima Antoni (JURNAL OLAHRAGA INDRAGIRI, 2018)
ABSTRACT Based on the observations of researchers in the field is seen that students SSB Yapora Pratama Pekanbaru Regency has the skills to play football that is still lacking. It is seen from the achievements they get still unsatisfactory. Therefore, they need to be given training approaches that can improve the basic tecnique of playing soccer. This study aims to look at the effect of exercise distributed practice and massed practice approach the game against the basic tecnique of playing soccer. The research is a quasi-experiment. The study population was all students SSB Yapora Pratama Pekanbaru Regency with totaling 90 people, while the technique to sample used in this study sampling jenuh technique so that 40 students were defined as samples that students 10-12 years age group. After that, the distribution group by matching. The instrument used was a football skills test consisting of four forms of the test that is dribbling, passing, shooting, and ball control test. The data obtained and analyzed by t-test (t-test). The results showed that: (1) Thereis a significant effect of exercise based on an distributed practice approach to the basic technique of playing football. (2) There is a significant effect of exercise is based on an massed practice approach to the basic technique to play the game of football, and (3) There is a difference between the effect of the distributed practice approach to the massed practice of the game where the distributed practice approach provides an effective influence compared with the massed practice approach to the game against the basic technique of playing football.